(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
With high recognized importance of women entrepreneurship especially in the emerging economies where the gender gap has to be addressed it is very important to investigate the various factors impacting the motivation of women to take their career in entrepreneurship. Hence this paper focuses on the analysis of various factors impacting the motivation of women to start their businesses. Qualitative research is used for this research where the data was collected from the previous research related to women entrepreneurial motivation (WEM). The relationship between the various factor influencing WEM were analysed. Also, the relationship between the opportunity recognition (OR) and WEM was analysed in the study. The various factors impacting the WEM such as individual and environmental factors and their link with entrepreneurial motivation and OR were analysed and summarized. The findings of this research will contribute to the WEM literature and inform policymakers to the necessity to enhance the factors impacting the motivation of women entrepreneurs through various practices and initiatives.